Integration of Islamic Science and Science in Schools: Studies on Learning Islamic Religious Education in the Digital Era - Firman Mansir (TADRIS: Jurnal Pendidikan Islam, 2022)
The purpose of this study is to determine the integration of Islamic science and general education in schools and find out its implementation factually. This research uses qualitative methods with descriptive types of research and approaches using literature studies. Data sources and collection are carried out using literature relevant to the research, such as national and international books or journals. The results showed that the integration of Islamic science and science is more suitable for schools under the auspices of religion, such as madrasahs, Islamic boarding schools, and schools with integrated Islamic information. The implementation of the integration of Islamic science and science in schools, namely the change in applicable learning methods, requires the involvement of parents and the equation of vision and mission, as well as an integrative model curriculum.